Design and manufacture of a Semi-Automatic Cassava Chips Slicing Machine - Sutopo; Devi Kusumawati (Journal of Applied Mechanical Engineering Innovation, 2025)
Cassava is one of the commodities that is widely processed in Pagerharjo village, especially by the Madu Lestari Women Farmers Group (WFG). The problem found in WFG is that the production process of cassava chips is still done manually and has not been touched by the appropriate technology desired by KWT. This affects the capacity produced in production not much and limits labor. The purpose of this research is to explain the design process or design, explain the process of machining and test and analyze the factual capacity produced by the semi-automatic system cassava chips slicing machine. The research method used is research and development. The research process starts from observation, needs analysis, design, machine building, assembly, performance testing, data collection and analysis. Data analysis uses descriptive and quantitative theoretical considerations. The results of the study produced a cassava chips slicing machine semi-automatic system capable of producing a production capacity of 62.1 kg/h with a driving motor power of ¼ Hp.